The complexity and difficulty of diagnosing lung cancer: findings from a national primary-care study in Wales. Issue 5 (8th December 2014) - Neal, Richard D.; Robbé, Iain J.; Lewis, Malcolm; Williamson, Ian; Hanson, Jane
<x content-type="archive" xml:space="preserve">Abstract</x> Aim This paper aims to provide a detailed analysis of the diagnostic process of lung cancer from a primary-care perspective. Background Diagnosing lung cancer at a stage where curative treatment is possible remains a challenge. Beginning to understand the complexity and difficulty in the diagnostic journey should enable the development of interventions in order to facilitate timelier diagnosis. Methods A national study of significant events was conducted whereby general practitioners (GPs) in Wales were asked to report data relating to the diagnostic process of recent lung cancer diagnoses using a standard template. Both qualitative and quantitative data were analysed. Findings Case reports were received from 96 general practices on 118 patients. A total of 96 patients (81.4%) presented with respiratory symptoms. A total of 79 patients (66.9%) had a GP-initiated X-ray before diagnosis. A total of 23 patients (19.5%) had a chest X-ray that did not initially show suspicion of lung cancer. A total of 25 patients (21.2%) were diagnosed after a GP-initiated acute admission. Analysis of free-text qualitative data showed that, for many patients, their GP behaved in an exemplary manner. However, for some patients, the GP could have made more of the opportunities presented for timelier diagnosis. There were a number of atypical and complex presentations, where the opportunities for more timely diagnosis were more limited. A variety of causes of diagnostic delays in secondary care were reported. These findings will inform health policy, and will inform the design of interventions to try to facilitate more timely diagnosis for symptomatic patients. We encourage greater compliance with diagnostic guidelines and greater vigilance for patients presenting with atypical symptoms, as well as for patients whose initial chest X-rays are normal.